Breaking Boundaries in Histone Modification MS-Based Detection: A Tailored Search Strategy for Unrestricted Identification of Novel Epigenetic Marks - Vai, Alessandro; Noberini, Roberta; Graziadei, Andrea; Polasky, Daniel A.; Yu, Fengchao; Nesvizhskii, Alexey I.; Bonaldi, Tiziana (Molecular & cellular proteomics, 2025)
Histone post-translational modifications (PTMs) play a crucial role in regulating gene expression and maintaining DNA integrity, and their aberrations are linked to various diseases, including cancer. While lysine acetylation and methylation have been extensively studied, recent research has uncovered additional PTMs that significantly contribute to chromatin structure and function. Mass spectrometry is the most effective analytical method for studying histone PTMs; however, computational limitations often restrict the analysis to common modifications. Unrestrictive search strategies have the potential to enable a more comprehensive characterization of the histone modification landscape. In this work, we systematically assess the application of unrestrictive search approaches to histone data. After evaluating the limitations of these methods, we develop a novel bioinformatics workflow, named HiP-Frag (histone PTM analysis with FragPipe), which enables the identification of 96 sites decorated with uncommon PTMs on core histones—60 of which were previously unreported—as well as 55 histone marks on linker histones, including 13 novel ones, purified from human cell lines and primary samples. The expanded histone PTM analysis enabled by this strategy is among the first to extract previously unexplored epigenetic information from mass spectrometry raw data. This approach paves the way for a facilitated and more streamlined identification of uncommon and yet unannotated histone modifications, supporting a deeper dissection of the histone code and the understanding of the potential biological role of the novel epigenetic marks. [Display omitted] •Novel histone post-translational modifications (PTMs) have emerged as regulators of chromatin structure.•Histone PTM analysis with FragPipe (HiP-Frag) is a workflow integrating closed, open, and detailed mass offset searches.•HiP-Frag simplifies the discovery of novel histone modifications.•HiP-Frag identified 60 novel PTMs on core histones and 13 on linker histones. This study introduces and describes HiP-Frag, a bioinformatics workflow that exploits unrestrictive search strategies to expand the analysis of histone post-translational modifications (PTMs) to unknown ones, from mass spectrometry data. By expanding the catalog of histone PTMs with 60 marks on core histones and 13 on linker histones, HiP-Frag enables a more comprehensive investigation of the histone code, giving access to previously unexplored epigenetic information.